2 liquid-curing adhesive composition
Patent Information
- Application Number
- CN202280049588.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-26
- Filing Date
- 2022-07-12
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-07-12
AI Technical Summary
[0055]本发明的2液固化型粘接剂组合物能够兼顾高疲劳耐久性及高衰减性。
Smart Images

Figure CN117715998B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a two-component curing adhesive composition. Background Technology
[0002] Previously, in order to provide a two-component urethane adhesive composition that maintains excellent curing speed as a two-component type and has good adhesion and heat resistance, the following two-component urethane adhesive composition was disclosed. It is a two-component urethane adhesive composition having a main agent and a curing agent. The main agent contains an urethane prepolymer (A) having an isocyanate group. The curing agent contains a compound (B) having two or more active hydrogen groups in one molecule. At least one of the main agent and the curing agent contains a compound (C) having an isocyanurate ring and particles (D) with an average particle size of 0.1 to 10 μm. The particles (D) contain organic matter (Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-82118 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] In recent years, from the perspectives of extending the service life of adhesives and suppressing vibration, it is necessary to improve both the fatigue durability and degradation resistance of adhesives.
[0008] In this context, when the inventors of this application formulated and evaluated a two-component curing adhesive composition based on the aforementioned patent literature, they confirmed that simultaneously improving the fatigue durability and degradation resistance of such a composition is extremely difficult. This is because fatigue durability and degradation resistance are inversely related.
[0009] Therefore, the object of the present invention is to provide a two-component curing adhesive composition that can take into account both high fatigue durability and high attenuation.
[0010] Methods for solving problems
[0011] In order to solve the above-mentioned problems, the inventors of this application conducted in-depth research and found that by making at least one of the main agent and the curing agent containing the urethane prepolymer having isocyanate groups contain specific polymer particles, the desired effect can be obtained, thereby completing the present invention.
[0012] Based on the above insights, the present invention specifically addresses the aforementioned issues through the following configuration. [1]
[0014] A two-component curing adhesive composition comprising a base agent (A) and a curing agent (B), wherein the base agent (A) comprises a urethane prepolymer (a1) having isocyanate groups.
[0015] At least one of the above-mentioned main agent (A) and curing agent (B) contains polymer particles (X) with an average particle size of 0.01 to 200 μm.
[0016] The glass transition temperature of the aforementioned polymer particles (X) is in the range of -40℃ to +80℃.
[0017] The content of the aforementioned polymer particles (X) is 5% by mass or more of the total amount of the aforementioned two-component curing adhesive composition.
[0018] The loss tangent of the cured product (P) obtained by curing the above two-component curable adhesive composition is 0.15 or higher under the conditions of -40℃ to +80℃ and 100Hz.
[0019] In the tensile shear fatigue test conducted according to JIS K6864, the above-mentioned cured material (P) showed good performance under stress amplitude of 2.8 MPa and a repetition count of 10. 7 No fracture occurs under these conditions. [2]
[0021] According to the two-component curing adhesive composition described in [1], the elongation at break of the cured product (P) is 50% or more. [3]
[0023] According to the two-component curing adhesive composition described in [1] or [2], the curing agent (B) comprises a polyol compound (b1) and / or a polyamine compound (b2). [4]
[0025] According to the two-component curing adhesive composition described in [3], the polyol compound (b1) comprises at least one polyol compound selected from polyoxyethylene polyol, polyoxypropylene polyol, polyoxyethylene polyoxypropylene polyol, polybutadiene polyol, polyisoprene polyol, polyacrylic polyol, and partially modified compounds obtained by partially modifying each of these compounds. [5]
[0027] According to any one of [1] to [4], the two-component curing adhesive composition, the polymer particles (X) comprise a polymer obtained by reacting a polyisocyanate compound (x1) with at least one compound (x2) selected from polyol compounds, polyamine compounds and potential polyamine compounds. [6]
[0029] According to any one of [1] to [5], the two-component curing adhesive composition, the polymer particles (X) comprise a polymer obtained by reacting a maleic anhydride modified oligomer (x3) with at least one compound (x4) selected from polyol compounds, polyamine compounds and potential polyamine compounds. [7]
[0031] According to any one of [1] to [6], the tensile modulus of the cured product (M) obtained by curing the remaining portion of the two-component curable adhesive composition other than the polymer particles (X) is 5 MPa or more.
[0032] The minimum loss tangent of the polymer particles (X) measured under the conditions of temperature range of -40℃ to +80℃ and frequency of 100Hz is greater than 0.05. [8]
[0034] According to any one of [1] to [7], the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) with a polyol compound (a3) in such a manner that the equivalent ratio of the isocyanate group in the polyisocyanate compound (a2) to the hydroxyl group in the polyol compound (a3) is 1.5 to 14.
[0035] The curing agent (B) mentioned above contains a polyol compound (b1) and a polyamine compound (b2).
[0036] The equivalent ratio of isocyanate groups in the main agent (A) to the active hydrogen-containing groups in the curing agent (B) is 0.8 to 4.
[0037] The isocyanate group in the above-mentioned main agent (A) has an equivalent ratio of 1.2 to 6 to the amino group in the above-mentioned polyamine compound (b2). [9]
[0039] According to the two-component curing adhesive composition described in [8], the polyol compound (a3) comprises at least one polyol compound selected from polyester polyol, polytetramethylene ether glycol, polycarbonate polyol, polycaprolactone polyol, and partially modified compounds obtained by partially modifying each of these compounds.
[10]
[0041] The minimum loss tangent of the cured product (N) obtained by curing the remaining portion of the two-component curable adhesive composition (excluding the polymer particles (X)) according to any one of [1] to [6] is 0.05 or more, measured under the conditions of a temperature range of -40°C to +80°C and a frequency of 100Hz.
[0042] The tensile elastic modulus of the polymer microparticles (X) is 5 MPa or higher.
[11]
[0044] According to any one of [1] to [6] and
[10] , the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) with a polyol compound (a3) in such a manner that the equivalent ratio of the isocyanate group in the polyisocyanate compound (a2) to the hydroxyl group in the polyol compound (a3) is 1.5 to 2.5.
[0045] The curing agent (B) mentioned above contains a polyol compound (b1) and a polyamine compound (b2).
[0046] The equivalent ratio of isocyanate groups in the main agent (A) to the active hydrogen-containing groups in the curing agent (B) is 0.8 to 4.
[0047] The isocyanate group in the main agent (A) has an equivalent ratio of 1.5 to 8.0 to the amino group in the polyamine compound (b2).
[12]
[0049] According to the two-component curing adhesive composition of
[11] , the polyol compound (a3) comprises at least one polyol compound selected from polyoxypropylene glycol, polybutadiene polyol, polyisoprene polyol, polyacrylic acid polyol, and partially modified compounds obtained by partially modifying each of these compounds.
[13]
[0051] The maximum value of the loss tangent of the cured product (P) according to any one of [1] to
[12] is 0.3 or more, measured under the conditions of temperature range of -40°C to +80°C and frequency of 100Hz.
[14]
[0053] According to any one of [1] to
[13] , the polymer microparticles (X) are obtained by crosslinking a crosslinked oligomer or a crosslinked polymer in at least one medium selected from water, an organic solvent, an oligomer, and a polymer to produce polymer microparticles.
[0054] Invention Effects
[0055] The two-component curing adhesive composition of the present invention can achieve both high fatigue durability and high attenuation. Attached Figure Description
[0056] [ Figure 1 ] Figure 1 A schematic diagram illustrating an example of a cross-section of a cured product (P) obtained by curing the two-component curable adhesive composition of the present invention. Detailed Implementation
[0057] The present invention will now be described in detail.
[0058] It should be noted that in this specification, the range of values represented by “~” refers to the range of values recorded before and after “~”.
[0059] Unless otherwise specified in this specification, each component may be used individually or in combination of two or more substances. When a component contains two or more substances, the content of the component refers to the total content of the two or more substances.
[0060] In this specification, the phrase "at least one of high fatigue durability and high attenuation is superior" is sometimes expressed as "the effect of the present invention is superior".
[0061] [2-Liquid Curing Adhesive Composition]
[0062] The two-component curing adhesive composition of the present invention (the composition of the present invention) is the following two-component curing adhesive composition.
[0063] It is a two-component curing adhesive composition having a main agent (A) and a curing agent (B), wherein the main agent (A) comprises a urethane prepolymer (a1) having isocyanate groups.
[0064] At least one of the above-mentioned main agent (A) and curing agent (B) contains polymer particles (X) with an average particle size of 0.01 to 200 μm.
[0065] The glass transition temperature of the aforementioned polymer particles (X) is in the range of -40℃ to +80℃.
[0066] The content of the aforementioned polymer particles (X) is 5% by mass or more of the total amount of the aforementioned two-component curing adhesive composition.
[0067] The loss tangent of the cured product (P) obtained by curing the above two-component curable adhesive composition is 0.15 or higher under the conditions of -40℃ to +80℃ and 100Hz.
[0068] In the tensile shear fatigue test conducted according to JIS K6864, the above-mentioned cured material (P) showed good performance under stress amplitude of 2.8 MPa and a repetition count of 10. 7 No fracture occurs under these conditions.
[0069] The compositions of the present invention will now be described in detail.
[0070] The composition of the present invention is a two-component curing adhesive composition having a main agent (A) and a curing agent (B), wherein the main agent (A) comprises a urethane prepolymer (a1) having an isocyanate group.
[0071] <<Main Agent (A)>>
[0072] In this invention, the main agent (A) comprises a urethane prepolymer (a1) having isocyanate groups.
[0073] <Urethane prepolymer (a1)>
[0074] In this invention, the urethane prepolymer (a1) has isocyanate groups. Preferably, one molecule of urethane prepolymer (a1) has multiple isocyanate groups.
[0075] From the viewpoint of achieving better results from the present invention, it is preferred that the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) with a polyol compound (a3) in such a manner that the equivalent ratio (isocyanate group / hydroxyl group) of the isocyanate group in the polyisocyanate compound (a2) to the hydroxyl group in the polyol compound (a3) is 1.5 to 14.
[0076] The urethane prepolymer (a1) may also contain unreacted polyisocyanate compounds (a2).
[0077] (Polyisocyanate compound (a2))
[0078] Polyisocyanate compounds (a2) are compounds that have multiple isocyanate groups in one molecule.
[0079] The polyisocyanate compound (a2) is preferably an aromatic hydrocarbon compound having multiple isocyanate groups, and more preferably a diphenylmethane diisocyanate, etc.
[0080] (Polyol compound (a3))
[0081] Polyol compounds (a3) are compounds that have multiple hydroxyl groups in one molecule.
[0082] Examples of polyol compounds (a3) include, for example, polyoxyalkylene polyols such as polytetramethylene ether diol, polyoxyethylene polyol, polyoxypropylene polyol, and polyoxyethylene polyoxypropylene polyol; polycarbonate polyols; and polyisoprene polyols.
[0083] <<Curing Agent (B)>>
[0084] In this invention, curing agent (B) is a concept relative to main agent (A) in a two-component curing adhesive composition, referring to a general, broad curing agent.
[0085] The curing agent (B) typically contains a solid curing agent (in the narrow sense) that can react with the urethane prepolymer (a1) contained in the main agent (A).
[0086] As a solid curing agent (in the narrow sense) contained in curing agent (B), compounds having multiple active hydrogen groups can be cited.
[0087] Examples of groups containing active hydrogen include hydroxyl, amino, and imino groups.
[0088] From the viewpoint of achieving better results in this invention, the curing agent (B), in the narrow sense, preferably contains a polyol compound (b1) and / or a polyamine compound (b2), and more preferably contains both a polyol compound (b1) and a polyamine compound (b2).
[0089] (Polyol compound (b1))
[0090] Polyols (b1) are compounds that have multiple hydroxyl groups in one molecule.
[0091] From the viewpoint of achieving better results in this invention, the polyol compound (b1) preferably includes at least one polyol compound selected from polyoxyethylene polyol, polyoxypropylene polyol, polyoxyethylene polyoxypropylene polyol, polybutadiene polyol, polyisoprene polyol, polyacrylic acid polyol, and partially modified compounds obtained by partially modifying each of these compounds.
[0092] As a modification of polyol compound (b1), examples include compounds obtained by introducing a polyester chain in a block shape into the end of polyoxyethylene polyols exemplified above for polyol compound (b1). It should be noted that the modified product obtained using polyester described above may have multiple hydroxyl groups.
[0093] (Polyamine compound (b2))
[0094] Polyamine compounds (b2) are compounds that have multiple amino groups (NH2) in one molecule.
[0095] Examples of polyamine compounds (b2) include, for example, diethylmethylphenylenediamine (DETDA), 4,4'-methylenebis(2-chloroaniline), trimethylenebis(4-aminobenzoate), and dimethylthiotoluenediamine (DMTDA).
[0096] <<Polymer Microparticles (X)>>
[0097] In this invention, at least one of the main agent (A) and the curing agent (B) comprises polymer particles (X) with an average particle size of 0.01 to 200 μm.
[0098] At least one of the main agent (A) and the curing agent (B) may contain polymer particles (X), or both the main agent (A) and the curing agent (B) may each contain polymer particles (X). From the viewpoint of better performance of the present invention, it is preferable that at least the curing agent (B) contains polymer particles (X).
[0099] <Average particle size of polymer particles (X)>
[0100] In this invention, the average particle size of the polymer microparticles (X) is 0.01 to 200 μm.
[0101] From the viewpoint of achieving better results in this invention, the average particle size of the polymer microparticles (X) is preferably 0.1 μm to 100 μm.
[0102] (Method for determining the average particle size of polymer particles (X))
[0103] In this invention, the average particle size of the polymer particles (X) refers to the average value obtained by measuring the diameter of 10 polymer particles (X) randomly selected from those presented in a photograph taken at 2000x magnification using a scanning electron microscope (SEM).
[0104] <Glass transition temperature of polymer particles (X)>
[0105] In this invention, the glass transition temperature (Tg) of the polymer particles (X) is in the range of -40°C to +80°C. The aforementioned Tg range of -40°C to +80°C is sufficient.
[0106] From the viewpoint of achieving better results with the present invention, the above-mentioned Tg is preferably in the range of -35 to +55°C.
[0107] In this invention, the glass transition temperature (Tg) of the polymer microparticles (X) is obtained by the following method: when making the polymer microparticles (X), the medium described later is not used, and the remaining components are placed at 23°C and 55% RH (relative humidity) for 7 days to cure the above components and obtain a cured product (the cured product corresponds to (H) described later). For this cured product, dynamic viscoelasticity measurement (Dynamic Mechanical Analysis) is used to perform forced elongation vibration in the temperature range of -50°C to +120°C under the conditions of strain 0.01%, frequency 100Hz, and heating rate 5°C / min, and tanδ is measured. The temperature showing the peak value (maximum value) of tanδ is obtained from the measurement results.
[0108] (The polymer backbone that makes up the polymer particles (X))
[0109] There are no particular limitations on the backbone of the polymer constituting the polymer particles (X). Preferably, the backbone is a polyurethane or conjugated diene rubber.
[0110] The polyurethane serving as the aforementioned backbone is a polymer having urethane bonds and / or urea bonds (e.g., polymer particles 1-3, 5, 6 described later).
[0111] The conjugated diene rubber that forms the above-mentioned backbone only needs to contain at least a conjugated diene in the monomers constituting the conjugated diene rubber. Examples of conjugated diene rubbers include, for example, polybutadiene, polyisoprene, etc. (e.g., polymer particles 4 and 7 described later).
[0112] (crosslinking)
[0113] From the viewpoint of achieving better results in this invention, the polymer constituting the polymer particles (X) is preferably cross-linked.
[0114] As an example of the aforementioned crosslinking, the aforementioned backbones can be bonded together by, for example, urethane bonds, urea bonds, ester bonds, or amide bonds.
[0115] When the aforementioned backbone is polyurethane, crosslinking via urethane bonds or urea bonds is preferred.
[0116] When the skeleton is a conjugated diene rubber, crosslinking is preferably carried out through ester bonds or amide bonds, and more preferably through amide bonds.
[0117] (The cross-linking points are urethane bonds and / or urea bonds)
[0118] From the viewpoint of achieving better results from the present invention, as one of the preferred embodiments, it can be said that the polymer microparticles (X) comprise a polymer (e.g., polymer microparticles 1 to 3, 5, 6 described below) obtained by reacting a polyisocyanate compound (x1) with at least one compound (x2) selected from polyol compounds, polyamine compounds, and potential polyamine compounds.
[0119] • Polyisocyanate compounds (x1)
[0120] The polyisocyanate compound (x1) that can be used in the manufacture of polymer microparticles (X) is a compound having multiple isocyanate groups. The polyisocyanate compound (x1) preferably comprises a urethane prepolymer (e.g., the urethane prepolymers used in the manufacture of polymer microparticles 1 to 3, 5, and 6 described later). Examples of urethane prepolymers include, for instance, the same urethane prepolymer (a1) described above.
[0121] When the polyisocyanate compound (x1) contains a urethane prepolymer, it may also contain the polyisocyanate compound used in the manufacture of the urethane prepolymer. The polyisocyanate compound used in the manufacture of the urethane prepolymer may be an unreacted product during the manufacture or a polyisocyanate compound added after the manufacture.
[0122] • Compound (x2)
[0123] The compound (x2) that can be used in the manufacture of polymer microparticles (X) preferably includes at least one compound selected from polyol compounds, polyamine compounds and potential polyamine compounds (specifically, for example, the cases of polymer microparticles 1 to 3, 5 and 6 described later).
[0124] Polyol compounds
[0125] From the viewpoint of being able to manufacture polymer particles (X) more efficiently, one preferred approach is to have the polyol compound (x2) with a molecular weight of 3000 or less.
[0126] Examples of polyol compounds with a molecular weight of 3000 or less include, for example, low molecular weight polyols such as butanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, glycerol, trimethylolpropane, and triethanolamine; polyisoprene polyols, polybutadiene polyols, polyacrylic acid polyols, and polycarbonate polyols (specifically, for example, the cases of polymer particles 1 to 3 described later).
[0127] When the polyol compound (x2) is a polymeric polyol (e.g., the polyisoprene polyol mentioned above), the molecular weight of the polymeric polyol can be the number average molecular weight.
[0128] Polyamine compounds
[0129] The polyamine compound (x2), which can be used in the manufacture of polymer microparticles (X), is a compound having multiple amino groups (NH2) in one molecule. Examples of the polyamine compounds mentioned above include, for example, the same polyamine compound (b2) as the curing agent described above (specifically, for example, the cases of polymer microparticles 5 and 6 described later).
[0130] Potential polyamine compounds
[0131] Potential polyamine compounds (x2) that can be used in the manufacture of polymer microparticles (X) are compounds containing multiple potentially amino groups. Examples of potentially amino groups include... Azolidine ring. Examples of potential polyamine compounds, such as those represented by formula (1), can be cited. Azolidine compounds.
[0132]
[0133] In equation (1), R 1 R represents a hydrocarbon group. 2 This represents a linking group with a valence of m+n, where m is an integer from 1 to 6 and n is an integer from 0 to 4.
[0134] In equation (1) above, R 1 It represents a hydrocarbon group.
[0135] Examples of the aforementioned hydrocarbon groups include, for example, aliphatic hydrocarbon groups (straight-chain, branched, or cyclic), aromatic hydrocarbon groups, or combinations thereof.
[0136] From the viewpoint of achieving better results with the present invention, the above-mentioned hydrocarbon group is preferably an aliphatic hydrocarbon group, and more preferably an aliphatic hydrocarbon group with 5 to 15 carbon atoms.
[0137] In equation (1), R 2 This indicates a linking group with an m+n valence.
[0138] Examples of linking groups include hydrocarbon groups. Examples of hydrocarbon groups include aliphatic hydrocarbon groups (straight-chain, branched, or cyclic), aromatic hydrocarbon groups, or combinations thereof. These hydrocarbon groups may have heteroatoms such as oxygen, nitrogen, or sulfur atoms.
[0139] Examples of linking groups include aromatic aliphatic groups such as xylene.
[0140] In equation (1), m is an integer from 1 to 6. Considering the curing properties and physical properties of the cured product, 2 to 3 is particularly preferred.
[0141] In equation (1), n is an integer from 0 to 4. From the perspective of solidification, 0 to 1 is particularly preferred.
[0142] As mentioned above Examples of azole compounds include those represented by formula (IV) below.
[0143]
[0144] (The cross-linking points are ester bonds and / or amide bonds)
[0145] Furthermore, from the viewpoint of achieving better results from the present invention, as one of the preferred embodiments, it can be cited that the polymer microparticles (X) comprise a polymer obtained by reacting a maleic anhydride modified oligomer (x3) with at least one compound (x4) selected from polyol compounds, polyamine compounds and potential polyamine compounds (specifically, for example, the cases of polymer microparticles 4 and 7 described later).
[0146] • Maleic anhydride modified oligomers (x3)
[0147] The maleic anhydride-modified oligomer (x3) that can be used in the manufacture of polymer particles (X) is an oligomer having maleic anhydride groups. Examples of conjugated diene rubbers can be used as the backbone of the maleic anhydride-modified oligomer (x3). Examples of such conjugated diene rubbers include polybutadiene and polyisoprene.
[0148] • Compounds (x4)
[0149] The compound (x4) that can be used in the manufacture of polymer microparticles (X) is the same as the compound (x2) described above.
[0150] From the viewpoint of high reactivity with maleic anhydride modified oligomer (x3), compound (x4) preferably contains at least one compound selected from polyamine compounds and potential polyamine compounds, more preferably containing a potential polyamine compound.
[0151] <Polymer Particle (X) Content>
[0152] In this invention, the content of polymer microparticles (X) is 5% by mass or more of the total composition of this invention.
[0153] From the viewpoint of achieving better results from the present invention, the content of polymer microparticles (X) is preferably 5 to 30% by mass of the total composition of the present invention, more preferably 10 to 20% by mass.
[0154] It should be noted that the content of polymer particles (X) does not include the amount of the media described later that can be used in the manufacture of polymer particles (X).
[0155] (Method for manufacturing polymer microparticles (X))
[0156] As a method for manufacturing polymer microparticles (X), one example is the following method: crosslinking a crosslinked oligomer or a crosslinked polymer (the crosslinked oligomer or crosslinked polymer being the raw material for polymer microparticles (X)) in at least one medium selected from water, an organic solvent, an oligomer, and a polymer, thereby producing polymer microparticles.
[0157] • Cross-linked oligomers or cross-linked polymers (raw materials for polymer particles (X))
[0158] The crosslinkable oligomers used as raw materials for polymer particles (X) in the manufacture of polymer particles (X) are crosslinkable oligomers. The crosslinkable polymers used as raw materials for polymer particles (X) are crosslinkable polymers (excluding the aforementioned crosslinkable oligomers).
[0159] Regarding crosslinkable oligomers as raw materials for polymer particles (X), examples include urethane prepolymers as polyisocyanate compounds (x1) (e.g., urethane prepolymers used in the manufacture of polymer particles 1-3, 5, and 6 described later). Specifically, examples of the aforementioned urethane prepolymers include, for instance, urethane prepolymer (a1).
[0160] Regarding crosslinked polymers that serve as raw materials for polymer particles (X), examples include maleic anhydride-modified oligomers (x3), and more specifically, examples include maleic anhydride-modified polybutadiene (e.g., maleic anhydride-modified polybutadiene used in the manufacture of polymer particles 4 and 7 described later).
[0161] Crosslinking
[0162] The crosslinking of the crosslinked oligomers in the above-mentioned medium can be a case where the crosslinked oligomers crosslink with each other, or a case where the crosslinked oligomers crosslink with a crosslinking agent.
[0163] The crosslinking of crosslinked polymers in the aforementioned media is also the same.
[0164] Examples of crosslinking agents mentioned above include compounds (x2) and (x4).
[0165] Polymer particles (X) can be manufactured by reacting a mixture containing a crosslinked oligomer or crosslinked polymer, the aforementioned medium, and a crosslinking agent that may be used as needed, at a temperature of 20 to 40°C while stirring.
[0166] ·medium
[0167] The medium that can be used in manufacturing polymer particles (X) includes at least one medium selected from water, organic solvents, oligomers and polymers.
[0168] The aforementioned medium can be a dispersion medium used to disperse the polymer particles (X) after manufacturing the polymer particles (X).
[0169] From the viewpoint of achieving better results and being able to efficiently manufacture polymer particles (X) according to the present invention, the aforementioned medium preferably comprises oligomers and / or polymers, and more preferably oligomers. Examples of oligomers that can be used as the medium include urethane prepolymers and polyoxyalkylene polyols.
[0170] The medium used in manufacturing polymer particles (X) can be a medium that disperses the polymer particles (X) after manufacturing them. Alternatively, after manufacturing the polymer particles (X) in the presence of the medium, the medium can be further reacted while still containing the polymer particles (X), thereby dispersing the polymer particles (X) in the reacted medium.
[0171] It should be noted that, in this invention, "medium" refers to the medium used in manufacturing polymer particles (X), or the medium (dispersion medium) used to disperse polymer particles (X) after manufacturing them.
[0172] The medium is preferably liquid at room temperature (23°C).
[0173] Oligomers as a medium
[0174] When the main agent (A) contains polymer particles (X), from the viewpoint of achieving better results and efficiently manufacturing polymer particles (X) according to the present invention, the oligomer as the medium preferably contains a urethane prepolymer. Examples of urethane prepolymers as the medium include, for instance, the same urethane prepolymer (a1) described above. Furthermore, when manufacturing polymer particles (X), if, for example, the polyol compound (a3) described above is used as the medium, after the polymer particles (X) are formed and are in a state where the polymer particles (X) are dispersed in the polyol compound (a3), the polyisocyanate compound (a2) described above can be further added thereto, causing the polyisocyanate compound (a2) to react with the polyol compound (a3), thereby forming the urethane prepolymer as the final medium. In the above case, the polymer particles (X) can be dispersed in the urethane prepolymer as the final medium.
[0175] In addition, when the main agent (A) contains polymer particles (X) and a urethane prepolymer as a medium, part or all of the urethane prepolymer (a1) contained in the main agent (A) may be the urethane prepolymer as the medium mentioned above.
[0176] In the case where the main agent (A) contains polymer particles (X) and a urethane prepolymer as a medium, and a portion of the urethane prepolymer (a1) is the urethane prepolymer as the medium, a urethane prepolymer may be subsequently added to the mixture of polymer particles (X) and the urethane prepolymer as a medium.
[0177] On the other hand, when the curing agent (B) contains polymer particles (X), from the viewpoint of achieving better results with the present invention and being able to efficiently manufacture the polymer particles (X), the oligomer as the medium preferably contains a polyoxyalkylene polyol, more preferably a polyoxypropylene polyol and / or polytetramethylene glycol. Regarding the oligomer as the medium, the aforementioned polyoxypropylene polyol includes the concept of a polyoxyethylene polyoxypropylene polyol.
[0178] In addition, when the curing agent (B) contains polymer particles (X) and a polyoxyalkylene polyol as a medium, part or all of the polyol compound (b1) contained in the curing agent (B) may be the polyoxyalkylene polyol as the aforementioned medium.
[0179] In addition, if the curing agent (B) contains polymer particles (X) and a polyoxyalkylene polyol as a medium, and a portion of the polyol compound (b1) contained in the curing agent (B) is the aforementioned polyoxyalkylene polyol as a medium, a polyoxyalkylene polyol may be subsequently added to the mixture of polymer particles (X) and the polyoxyalkylene polyol as a medium.
[0180] In the combination of the medium and the raw material of the polymer particles (X) in the manufacture of polymer particles (X), it is preferable that the oligomer or polymer used as the medium is a different compound from the aforementioned crosslinked oligomer and crosslinked polymer and the crosslinking agent (compound (x2), compound (x4)) used as the raw material of the polymer particles (X).
[0181] When the main agent (A) contains polymer particles (X) and the polymer particles (X) are accompanied by a medium, from the viewpoint of excellent miscibility and storage stability in the main agent (A), the medium used to manufacture the polymer particles (X), i.e., the medium used to form the polymer particles (X), preferably contains an oligomer (polyoxyalkylene polyol) such as polytetramethylene glycol. The weight-average molecular weight of the oligomer is preferably less than 10,000. In addition, as described above, a polyisocyanate compound (a2) can be further added to the polyol compound (a3) in which the polymer particles (X) are dispersed, and the polyisocyanate compound (a2) reacts with the polyol compound (a3) to form a urethane prepolymer as the final medium, and the urethane prepolymer is used as urethane prepolymer (a1).
[0182] When the curing agent (B) contains polymer particles (X) and the polymer particles (X) are present in conjunction with the medium, from the viewpoint of excellent miscibility and storage stability in the curing agent (B), the medium used to manufacture the polymer particles (X) preferably contains an oligomer (polyoxypropylene glycol) such as polyoxypropylene glycol. The weight-average molecular weight of the oligomer is preferably less than 10,000.
[0183] When polymer particles (X) are present in conjunction with a medium, from the viewpoint of achieving better results and superior storage stability of the present invention, the amount of medium is preferably 70 to 400 parts by mass relative to 100 parts by mass of polymer particles (X), more preferably 100 to 400 parts by mass.
[0184] <Loss tangent of cured material (P)>
[0185] In this invention, the loss tangent of the cured product (P) obtained by curing the composition of this invention is 0.15 or more under the conditions of a temperature range of -40°C to +80°C and a frequency of 100Hz (hereinafter sometimes referred to as "specific conditions"). That is, the minimum value of the loss tangent of the cured product (P) measured under the condition of a frequency of 100Hz is 0.15 or more in the temperature range of -40°C to +80°C.
[0186] By ensuring that the loss tangent of the cured material (P) is 0.15 or greater under the specific conditions described above, the present invention exhibits excellent attenuation characteristics. The larger the value of the loss tangent of the cured material (P), the better the attenuation characteristics.
[0187] From the viewpoint of achieving better results with the present invention, the loss tangent (minimum) of the above-mentioned cured material (P) within the temperature range of -40°C to +80°C is preferably 0.2 or more under the above-mentioned specific conditions.
[0188] There is no particular limitation on the maximum value of the loss tangent of the cured product (P) measured under the specific conditions described above, but from the viewpoint of achieving better results in this invention and maintaining excellent elongation at break, it is preferable to be 0.3 or higher.
[0189] <Tensile Shear Fatigue Properties Test of Cured Material (P)>
[0190] In this invention, in the tensile shear fatigue property test conducted according to JIS K6864, the cured product (P) obtained by curing the composition of this invention exhibits a stress amplitude of 2.8 MPa and a repetition count of 10. 7 It does not break under the conditions of [unspecified conditions] (it can withstand [unspecified conditions]).
[0191] In this invention, the cured material (P) in the above-mentioned tensile shear fatigue characteristic test is subjected to a stress amplitude of 2.8 MPa and a repetition count of 10. 7 If no fracture occurs under the given conditions, the fatigue durability of the present invention is considered excellent. Furthermore, in addition to increasing the stress amplitude compared to 2.8 MPa, the same procedure as described above is followed, with each increase in stress amplitude at 10... 7 Tensile shear fatigue characteristics tests were conducted with repeated cycles. The greater the stress amplitude at the initial fracture of the cured material (P) compared to 2.8 MPa, the better the fatigue durability was evaluated.
[0192] (Elongation at break of the cured product (P))
[0193] From the viewpoint of superior fatigue durability, the elongation at break of the cured product (P) obtained by curing the composition of the present invention is preferably 50% or more, more preferably 100 to 1000%.
[0194] (Method of curing (P))
[0195] The cured product (P) obtained by curing the composition of the present invention may have polymer microparticles (X) and a matrix other than polymer microparticles (X) in the composition of the present invention.
[0196] The portion of the composition of the present invention after removing only the polymer particles (X) is sometimes referred to as the “matrix” (the same applies hereinafter).
[0197] It should be noted that, in the present invention, when the polymer particles (X) are used in the form of a mixture with the above-described medium, the portion of the composition of the present invention other than the polymer particles (X) and the above-described medium is sometimes referred to as the "remaining portion" (hereinafter the same).
[0198] The cured product (P) obtained by curing the composition of the present invention will be described below with reference to the accompanying drawings. It should be noted that the present invention is not limited to the accompanying drawings.
[0199] Figure 1 A schematic diagram illustrating an example of a cross-section of a cured product (P) obtained by curing the two-component curable adhesive composition of the present invention.
[0200] exist Figure 1 In this invention, the cured product (P) 10 of the two-component curing adhesive composition has polymer microparticles (X) 14 and a cured product 12 of the matrix other than the polymer microparticles (X) in the composition of this invention.
[0201] The inventors of this application have discovered that by giving a cured product (P) polymer particles (X) and a matrix (part other than polymer particles (X)) and imparting fatigue durability or attenuation to both respectively, fatigue durability and attenuation, which are inversely related in the cured product (P), can be balanced.
[0202] That is, when the polymer particles (X) mainly bear the attenuation property, the matrix mainly bears the fatigue durability property; when the polymer particles (X) mainly bear the fatigue durability property, the matrix mainly bears the attenuation property.
[0203] As described above, by having polymer microparticles (X) and a matrix with different functions, the composition of the present invention can achieve both high fatigue durability and high attenuation as a whole.
[0204] In this specification, the case in which the polymer particles (X) mainly bear the attenuation property and the matrix mainly bears the fatigue durability property is sometimes referred to as "Method 1", and the case in which the polymer particles (X) mainly bear the fatigue durability property and the matrix mainly bears the attenuation property is referred to as "Method 2".
[0205] From the viewpoint of achieving better results with respect to the solidified product (P), method 1 is preferred.
[0206] Furthermore, the inventors of this application have found that, preferably, the tensile elastic modulus of the cured product (P) having fatigue durability is 5 MPa or more, and the minimum loss tangent of the cured product having attenuation under the above-mentioned specific conditions is 0.05 or more.
[0207] In the above-described case, the cured portion exhibiting fatigue durability has a loss tangent under the specific conditions described above, the minimum of which is preferably less than 0.15. Furthermore, the tensile modulus of the cured portion exhibiting attenuation is generally preferably less than 5 MPa.
[0208] To ensure that the tensile modulus of the cured product (P) having fatigue durability (the matrix or the remaining cured product in method 1, or the polymer particles (X) in method 2) is 5 MPa or more, examples of such methods include: making the index of the urethane prepolymer (a1) in method 1 3.5 or more; using the polyol compound (a3) used in the manufacture of the urethane prepolymer (a1) in method 1 or the hydrocarbon group of the urethane prepolymer used as the raw material for the polymer particles (X) in method 2 in a linear form (e.g., polyoxyethylene polyol, PTMG); and using a compound having 3 or more active hydrogen atoms as a curing agent in the curing agent (B) (preferably, the amount of the above-mentioned compound used in the matrix of method 1 is greater than that in method 2).
[0209] From the viewpoint of achieving better results in this invention, the minimum value of the loss tangent of the cured product (P) having a decaying portion (polymer particles (X) in method 1, or the matrix or remaining portion of the cured product in method 2) under the specific conditions described above is preferably 0.05 or more, and more preferably 0.15 or more.
[0210] To ensure that the minimum loss tangent of the cured product (P) having a decaying portion is 0.05 or more (more preferably 0.15 or more) under the specific conditions described above, examples of such methods can be employed, such as: making the index of the urethane prepolymer (a1) in manufacturing method 2 3.0 or less; using a polyol compound (a3) whose hydrocarbon group is branched (e.g., polyoxypropylene polyol, polyisoprene polyol) when constituting the urethane prepolymer (a1) in manufacturing method 2 or the urethane prepolymer used as a raw material for polymer particles (X) in method 1; and using a compound having 2 or fewer active hydrogen atoms as a curing agent in the narrow sense in the curing agent (wherein, it is preferable that the amount of the above-mentioned compound used in the matrix of method 2 is less than that of method 1).
[0211] Method 1
[0212] In the cured product (P) of the composition of the present invention, where the polymer particles (X) mainly bear the attenuation property and the matrix mainly bears the fatigue durability property (method 1), from the viewpoint of having better effects than the present invention, it is preferable that the cured product (M) obtained by curing the matrix other than the polymer particles (X) in the composition of the present invention (when the polymer particles (X) are accompanied by a medium, it is the part of the composition of the present invention other than the polymer particles (X) and the medium) has a tensile elastic modulus of 5 MPa or more, and the minimum value of the loss tangent of the polymer particles (X) measured under the conditions of temperature range of -40°C to +80°C and frequency of 100 Hz is 0.05 or more.
[0213] Loss tangent of polymer particles (X) in Method 1
[0214] ...minimum value of loss tangent
[0215] Regarding method 1, from the viewpoint of achieving better results according to the present invention, the minimum value of the loss tangent of the polymer particles (X) is preferably 0.05 or more under the specific conditions described above, more preferably 0.15 or more, and even more preferably 0.2 or more.
[0216] ...the maximum value of the loss tangent
[0217] Regarding method 1, from the viewpoint of achieving better results according to the present invention, the maximum value of the loss tangent of the polymer particles (X) is preferably 0.3 or more under the specific conditions described above, more preferably 0.5 or more, and even more preferably 0.8 or more.
[0218] In Method 1, there is no particular limitation on the upper limit of the loss tangent of the polymer particles (X) under the specific conditions described above, but from the viewpoint of achieving better results in this invention and maintaining excellent elongation at break, it is preferably 2.0 or less, and more preferably 1.5 or less.
[0219] Tensile elastic modulus of polymer microparticles (X) in Method 1
[0220] In method 1, from the viewpoint of achieving better results according to the present invention, the tensile elastic modulus of the polymer microparticles (X) is preferably 0.5 to 50 MPa.
[0221] Example of polymer particles (X) in Method 1
[0222] As the polymer particles (X) in Method 1, for example, they are reactants of polyisocyanate compound (x1) or maleic anhydride modified oligomer (x3) and compound (x2), as long as the minimum loss tangent of the reactants is 0.05 or more under the specific conditions described above, and the glass transition temperature of the reactants is -40°C to +80°C, there are no particular restrictions.
[0223] Examples of urethane prepolymers that can be used as the aforementioned polyisocyanate compound (x1) include, for example, aromatic polyisocyanates such as MDI reacted with at least one polyol selected from polyoxyalkylene polyols (e.g., polyoxypropylene polyol, polyoxyethylene polyol, polytetramethylene ether glycol), polycarbonate polyols, and polyisoprene polyols.
[0224] The maleic anhydride-modified oligomer (x3) described above is the same as described above. The maleic anhydride-modified oligomer (x3) preferably contains maleic anhydride-modified polybutadiene.
[0225] The same applies to the compound (x2) mentioned above.
[0226] As one preferred method, one can exemplify this by reacting a polyol compound (x2) with a polyisocyanate compound (x1) to form the polymer particles (X) of method 1. The polyol compound preferably comprises a low-molecular-weight polyol such as butanediol.
[0227] Furthermore, when reacting the polyamine compound (x2) with the polyisocyanate compound (x1) to form the polymer particles (X) of method 1, the molar ratio (index) of the isocyanate group present in (x1) to the amino group (NH2 group) present in the polyamine compound can be adjusted such that the minimum loss tangent of the obtained polymer particles (X) is 0.05 or more under the specific conditions described above, and the glass transition temperature is -40°C to +80°C.
[0228] When the potential polyamine (x2) is reacted with the maleic anhydride-modified oligomer (x3) to form the polymer particles (X) of method 1, the molar ratio (index) of the maleic anhydride group in (x3) to the amino group (NH2 group) in the potential polyamine compound can be adjusted such that the minimum loss tangent and the glass transition temperature of the obtained polymer particles (X) are within the ranges mentioned above.
[0229] Tensile elastic modulus of cured product (M) of Method 1
[0230] Regarding method 1, from the viewpoint of achieving better results according to the present invention, the tensile modulus of the cured product (M) obtained by curing the matrix (excluding polymer particles (X) in the composition of the present invention or the remaining part in the composition of the present invention excluding polymer particles (X) and the medium) is preferably 5 MPa or more, and more preferably 100 to 250 MPa.
[0231] The loss tangent of the cured product (M) of Method 1
[0232] In method 1, from the viewpoint of achieving better results according to the present invention, the loss tangent of the above-mentioned cured material (M) is preferably in the range of 0.05 to 0.2 under the above-mentioned specific conditions, and more preferably in the range of 0.05 or more and less than 0.15.
[0233] Example of cured product (M) of Method 1
[0234] In method 1, from the viewpoint of achieving better results and enabling the cured product (M) to have a tensile modulus of elasticity of 5 MPa or higher, it is preferable that the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) with a polyol compound (a3) such that the equivalent ratio (NCO / OH) of the isocyanate group in the polyisocyanate compound (a2) to the hydroxyl group in the polyol compound (a3) is 1.5 to 14.
[0235] The curing agent (B) contains a polyol compound (b1) and a polyamine compound (b2).
[0236] The equivalent ratio of isocyanate groups in the main agent (A) to the active hydrogen-containing groups in the curing agent (B) is 0.8–4.
[0237] The isocyanate group in the main agent (A) has an equivalent ratio of 1.2 to 6 to the amino group in the polyamine compound (b2).
[0238] It should be noted that, in the case where the polymer particles (X) are added to the curing agent (B) along with the polyol serving as a medium, the amount of active hydrogen groups in the polyol serving as a medium is included in the amount of active hydrogen groups in the curing agent (B) (the same applies below. Also, the same applies in method 2).
[0239] (Suitable method for curing the product (M) of Method 1)
[0240] From the viewpoint of achieving better results from the present invention, the above-mentioned equivalent ratio (NCO / OH) when manufacturing the urethane prepolymer (a1) is preferably 3 to 14, more preferably 4 to 10.
[0241] From the viewpoint of achieving better results with the present invention, the equivalent ratio of isocyanate groups in the main agent (A) to active hydrogen-containing groups in the curing agent (B) is preferably 0.5 to 4.
[0242] From the viewpoint of achieving better results in this invention, the equivalent ratio of the isocyanate group in the main agent (A) to the amino group in the polyamine compound (b2) is preferably 0.8 to 4.
[0243] In method 1, from the viewpoint that the present invention has better effects and that the tensile modulus of the cured product (M) is 5 MPa or more, the polyol compound (a3) used in manufacturing the urethane prepolymer (a1) preferably includes at least one polyol compound selected from polyester polyol, polytetramethylene ether glycol, polycarbonate polyol, polycaprolactone polyol, and partially modified products obtained by partially modifying each of these compounds.
[0244] As a modification of polyol compounds (a3), examples include the introduction of functional groups such as methyl groups.
[0245] Method 2
[0246] In the cured product (P) of the composition of the present invention, where the polymer particles (X) mainly bear the fatigue durability and the matrix mainly bears the attenuation (method 2), from the viewpoint of having better effects than the present invention, it is preferable that the cured product (N) obtained by curing the remaining part of the composition of the present invention other than the polymer particles (X) has a minimum loss tangent of 0.05 or more measured under the conditions of temperature range of -40°C to +80°C and frequency of 100Hz, and the tensile elastic modulus of the polymer particles (X) is 5 MPa or more.
[0247] Loss tangent of the cured product (N) in Method 2
[0248] ...minimum value of loss tangent
[0249] Regarding method 2, from the viewpoint of achieving better results according to the present invention, the minimum value of the loss tangent of the cured product (N) obtained by curing the matrix (excluding polymer particles (X) in the composition of the present invention, or the remaining part in the composition of the present invention excluding polymer particles (X) and the medium) is preferably 0.05 or more under the specific conditions described above, more preferably 0.1 or more, and even more preferably 0.2 or more.
[0250] ...the maximum value of the loss tangent
[0251] Regarding method 2, from the viewpoint of achieving better results according to the present invention, the maximum value of the loss tangent of the cured material (N) is preferably 0.3 or more under the specific conditions described above, more preferably 0.5 or more, and even more preferably 0.6 or more.
[0252] In method 2, there is no particular limitation on the upper limit of the loss tangent of the cured material (N) under the specific conditions described above, but from the viewpoint that the present invention is more effective and can maintain excellent elongation at break, it is preferably 2.0 or less, and more preferably 1.0 or less.
[0253] It should be noted that, as described above, when the polymer particles (X) are used in the form of a mixture with the aforementioned medium, the remaining portion refers to the portion of the composition of the present invention other than the polymer particles (X) and the aforementioned medium.
[0254] Tensile elastic modulus of cured product (N) of Method 2
[0255] In method 2, from the viewpoint of achieving better results according to the present invention, the tensile modulus of the cured material (N) is preferably 0.5 to 50 MPa.
[0256] Tensile elastic modulus of polymer microparticles (X) in Method 2
[0257] In method 2, from the viewpoint of achieving better results according to the present invention, the tensile elastic modulus of the polymer microparticles (X) is preferably 5 MPa or more, more preferably 70 to 300 MPa, and even more preferably 100 to 250 MPa.
[0258] Loss tangent of polymer particles (X) in Method 2
[0259] In method 2, from the viewpoint of achieving better results according to the present invention, the loss tangent of the polymer microparticles (X) is preferably in the range of 0.05 to 0.4 under the specific conditions described above, and more preferably in the range of 0.1 or more and less than 0.15.
[0260] Example of cured product (N) in Method 2
[0261] In method 2, from the viewpoint that the present invention has superior effects and that the minimum value of the loss tangent of the cured product (N) is 0.05 or more (more preferably 0.1 or more), it is preferable that the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) and a polyol compound (a3) in such a way that the equivalent ratio of the isocyanate group in the polyisocyanate compound (a2) to the hydroxyl group in the polyol compound (a3) is 1.5 to 2.5.
[0262] The curing agent (B) contains a polyol compound (b1) and a polyamine compound (b2).
[0263] The equivalent ratio of isocyanate groups in the main agent (A) to the active hydrogen-containing groups in the curing agent (B) is 0.8–4.
[0264] The isocyanate group in the main agent (A) has an equivalent ratio of 1.5 to 8.0 to the amino group in the polyamine compound (b2).
[0265] (Suitable method for curing (N) in Method 2)
[0266] From the viewpoint of achieving better results with the present invention, the equivalent ratio of isocyanate groups in the main agent (A) to active hydrogen-containing groups in the curing agent (B) is preferably 0.5 to 4.
[0267] From the viewpoint of achieving better results in this invention, the equivalent ratio of the isocyanate group in the main agent (A) to the amino group in the polyamine compound (b2) is preferably 2 to 8.
[0268] In method 2, the polyol compound (a3) preferably includes at least one polyol compound selected from polyoxypropylene glycol, polybutadiene polyol, polyisoprene polyol, polyacrylic acid polyol, and partially modified compounds obtained by partially modifying each of these compounds.
[0269] As a modification of polyol compounds (a3), examples include the introduction of functional groups such as methyl groups.
[0270] (additive)
[0271] The compositions of the present invention may further contain additives. Examples of additives include fillers such as carbon black, calcium carbonate, and silica, plasticizers, and anti-aging agents. The type and amount of additives can be suitably selected. The inclusion of each additive in either the main agent (A) or the curing agent (B) can be suitably selected.
[0272] (Manufacturing method)
[0273] As a method for manufacturing the composition of the present invention, an example of such a method is as follows: a mixture of a urethane prepolymer (a1) and an additive that may be used as appropriate is prepared as a main agent (A), and on the other hand, a mixture of a curing agent in the narrow sense and an additive that may be used as appropriate is prepared as a curing agent (B). During the above preparation, polymer particles (X) are added to at least one of the main agent (A) and the curing agent (B).
[0274] When polymer particles (X) are added to the main agent (A), the polymer particles (X) are preferably a mixture with a urethane prepolymer (as a medium). Furthermore, the polymer particles (X) preferably have isocyanate groups.
[0275] When polymer particles (X) are added to the curing agent (B), the polymer particles (X) are preferably a mixture with a polyoxyalkylene polyol such as polypropylene glycol (as a medium).
[0276] (How to use)
[0277] The composition of the present invention can be prepared by mixing the main agent (A) and the curing agent (B).
[0278] (use)
[0279] The compositions of the present invention can be used as adhesives.
[0280] Examples of substrates for using the compositions of the present invention include metals, plastics, rubber, and glass.
[0281] When using the composition of the present invention to bond the first substrate and the second substrate, it is preferable that either or both of the first substrate and the second substrate are metal.
[0282] The compositions of the present invention can be used, for example, as adhesives for automobiles and adhesives for shock resistance.
[0283] Example
[0284] The following examples illustrate the invention in detail. However, the invention is not limited thereto.
[0285] <<Synthesis of Carbamate Prepolymers>>
[0286] <Synthesis of Carbamate Prepolymer 1>
[0287] Under a nitrogen atmosphere, 100 g of polytetramethylene ether glycol (PTMG1000 (weight average molecular weight 1000, OH difunctional), manufactured by Mitsubishi Kemical Co., Ltd., hereinafter the same) and 100 g of 4,4'-diphenylmethane diisocyanate (index 4.0) were stirred at 80 °C for 4 hours to allow them to react, thus synthesizing urethane prepolymer 1.
[0288] It should be noted that the index used in the manufacture of urethane prepolymers is the equivalent ratio (molar ratio) of the NCO groups in the polyisocyanate compound (a2) to the OH groups in the polyol compound (a3) (the same applies below).
[0289] <Synthesis of Carbamate Prepolymer 2>
[0290] Under a nitrogen atmosphere, 100 g of polytetramethylene ether glycol and 150 g of 4,4'-diphenylmethane diisocyanate (index 6.0) were stirred at 80 °C for 4 hours to allow them to react and synthesize urethane prepolymer 2.
[0291] <Synthesis of Carbamate Prepolymer 3>
[0292] Under a nitrogen atmosphere, 100 g of polycarbonate diol (Duranol T6001 (weight average molecular weight of 1000), manufactured by Asahi Kasei Corporation, OH is difunctional) and 50 g of 4,4'-diphenylmethane diisocyanate (index of 2.0) were stirred at 80 °C for 4 hours to allow them to react and synthesize urethane prepolymer 3.
[0293] <Synthesis of Carbamate Prepolymer 4>
[0294] Under a nitrogen atmosphere, 100 g of polyoxypropylene glycol (Sannico FA-921 (hydroxyl value 27.9 mg / KOH g), OH is difunctional, manufactured by Sanyo Chemical Co., Ltd.) and 16 g of 4,4'-diphenylmethane diisocyanate (index 2.5) were stirred at 80 °C for 4 hours to allow them to react and synthesize urethane prepolymer 4.
[0295] <Synthesis of Carbamate Prepolymer 5>
[0296] Under a nitrogen atmosphere, 100 g of polyisoprene polyol (Poly ip (number average molecular weight of 2500, OH with 2 functional groups), manufactured by Idemitsu Kosan Co., Ltd.) and 14 g of 4,4'-diphenylmethane diisocyanate (index of 2.0) were stirred at 80 °C for 4 hours to allow the reaction to proceed, thus synthesizing urethane prepolymer 5.
[0297] Synthesis of Polymer Microparticles (X)
[0298] <Synthesis of Polymer Microparticle 1>
[0299] In 311g of polyoxypropylene glycol (Sanikis GL-3000, manufactured by Sanyo Chemical Co., Ltd. OH is trifunctional; the same applies hereinafter), under a nitrogen atmosphere and at room temperature (23°C; the same applies hereinafter), 151g of urethane prepolymer 3 and 5g of 1,4-butanediol were stirred for 3 hours to induce a crosslinking reaction, synthesizing polymer particles 1 dispersed in polyoxypropylene glycol. The index (molar ratio of NCO groups to OH groups) of the above raw materials was 0.52. The OH groups in the above index are the sum of the OH groups present in the above medium and 1,4-butanediol (the same applies in the synthesis of the polymer particles below). The crosslinking points generated by the above crosslinking reaction have urethane bonds.
[0300] The average particle size of polymer particles 1 is 10 μm, and the concentration of polymer particles 1 in the above dispersion (the total amount of polymer particles 1 dispersed in polyoxypropylene glycol) is 56% by mass. The glass transition temperature of polymer particles 1 is +40°C. Polymer particles 1 theoretically possess hydroxyl groups as active hydrogen groups. The medium (polyoxypropylene glycol) in the above dispersion is liquid at 23°C.
[0301] <Synthesis of Polymer Microparticles 2>
[0302] In 183g of polyoxypropylene glycol (Sunnyx GL-3000) as a medium, 119g of urethane prepolymer 4 and 3g of 1,4-butanediol were stirred for 3 hours at room temperature under a nitrogen atmosphere to induce a crosslinking reaction, synthesizing polymer particles 2 dispersed in polyoxypropylene glycol. The index (molar ratio of NCO groups to OH groups) of the above raw materials was 0.32. The crosslinking points generated by the above crosslinking reaction have urethane bonds.
[0303] The average particle size of polymer particles 2 is 2 μm, and the concentration of polymer particles 2 in the above dispersion is 46% by mass. The glass transition temperature of polymer particles 2 is -30°C. Polymer particles 2 theoretically possess hydroxyl groups as active hydrogen groups. The medium (polyoxypropylene glycol) in the above dispersion is liquid at 23°C.
[0304] <Synthesis of Polymer Microparticles 3>
[0305] In 260g of polyoxypropylene glycol (Sunnyx GL-3000) as a medium, 125g of urethane prepolymer 5 and 5g of 1,4-butanediol were stirred for 3 hours at room temperature under a nitrogen atmosphere to induce a crosslinking reaction, thereby synthesizing polymer particles 3 dispersed in polyoxypropylene glycol. The index (molar ratio of NCO groups to OH groups) of the above raw materials was 0.34. The crosslinking points generated by the above crosslinking reaction have urethane bonds.
[0306] The average particle size of polymer particles 3 is 5 μm, and the concentration of polymer particles 3 in the above dispersion is 40% by mass. The glass transition temperature of polymer particles 3 is -20 °C. Polymer particles 3 theoretically possess hydroxyl groups as active hydrogen groups. The medium (polyoxypropylene glycol) in the above dispersion is liquid at 23 °C.
[0307] <Synthesis of Polymer Microparticles 4>
[0308] In 80g of polyoxypropylene glycol (Sannic GL-3000) as a medium, under atmospheric conditions and at room temperature, 40g of maleic anhydride-modified polybutadiene (POLYVEST OC800S, manufactured by Ebonick Co., Ltd.) and 2g of [unclear text - possibly a chemical compound] having the following structure Azolidine compounds (such as 3-(2-hydroxyethyl)-2-(1-methylbutyl) The reactant is obtained by reacting azole (5BO, manufactured by Toyo Synthetic) with phenylene diisocyanate (XDI) in a molar ratio of 2:1. The azole ring hydrolyzes due to moisture in the air, generating a diamine with two amino groups (-NH2) derived from the above hydrolysis. The mixture is stirred for 3 hours (as follows) to allow for a cross-linking reaction, synthesizing polymer particles 4 dispersed in polyoxypropylene glycol. The molar ratio of maleic anhydride groups to NH2 groups in the above raw materials is 1.0. The cross-linking points formed by the above cross-linking reaction have amide bonds.
[0309] The average particle size of polymer particles 4 is 10 μm, and the concentration of polymer particles 4 in the above dispersion is 34% by mass. The glass transition temperature of polymer particles 4 is -30°C. The medium (polyoxypropylene glycol) in the above dispersion is liquid at 23°C.
[0310]
[0311] <Synthesis of Polymer Microparticles 5>
[0312] In 600g of polyoxypropylene glycol (Sunnyx GL-3000) as a medium, under a nitrogen atmosphere, 250g of urethane prepolymer 2 and 80g of DETDA (diethylmethylphenylenediamine) were stirred for 3 hours at room temperature to induce a crosslinking reaction, synthesizing polymer particles 5 dispersed in polyoxypropylene glycol. The index [molar ratio of NCO groups / (OH+NH2 groups)] of the above raw materials was 0.65. The crosslinking points generated by the above crosslinking reaction have urethane bonds.
[0313] The average particle size of polymer particles 5 is 3 μm, the concentration of polymer particles 5 in the above dispersion is 40% by mass, and the glass transition temperature is -20 °C. The polymer particles 5 theoretically possess amino groups as active hydrogen groups.
[0314] It should be noted that, in polymer particles, the amino group containing an active hydrogen group refers to a group in which a hydrogen atom is bonded to a nitrogen atom. This amino group does not include urethane bonds, urea bonds, or amide bonds (the same applies below).
[0315] The medium (polyoxypropylene glycol) in the above dispersion is in a liquid state at 23°C.
[0316] <Synthesis of Polymer Microparticle 6>
[0317] In 150g of polytetramethylene ether glycol (PTMG1000) as a medium, 120g of urethane prepolymer 2 and 9g of DETDA (diethylmethylphenylenediamine) were stirred for 3 hours at room temperature under a nitrogen atmosphere to allow for crosslinking reaction (the index [molar ratio of NCO groups / (OH+NH2 groups)] of the above raw materials was 0.2). In the reaction of urethane prepolymer 2 and DETDA, the above-mentioned polytetramethylene ether glycol functioned as a medium. After the reaction, 150g of 4,4'-diphenylmethane diisocyanate was further added to the mixture of urethane prepolymer 2, DETDA, and the above-mentioned polytetramethylene ether glycol. The mixture was stirred at 80°C for 4 hours under a nitrogen atmosphere to allow for reaction, ultimately synthesizing polymer particles 6 dispersed in the urethane prepolymer.
[0318] Polymer microparticles 6 mainly comprise the reactants of the aforementioned urethane prepolymer 2 and DETDA. In polymer microparticles 6, the crosslinking points generated through the reaction (crosslinking reaction) have urea bonds and / or urethane bonds.
[0319] The polymer particles 6 are ultimately dispersed in the urethane prepolymer, which serves as the final medium. The urethane prepolymer mainly comprises the urethane prepolymer obtained by reacting the polytetramethylene ether glycol used in the crosslinking reaction with 150g of 4,4'-diphenylmethane diisocyanate added after the crosslinking reaction. The final medium (urethane prepolymer) in the dispersion is liquid at 23°C.
[0320] The average particle size of polymer particles 6 is 8 μm, and the concentration of polymer particles 6 in the above dispersion is 28% by mass. The glass transition temperature of polymer particles 6 is -20 °C. Polymer particles 6 theoretically possess isocyanate groups.
[0321] <Synthesis of Polymer Microparticles 7>
[0322] In 292g of polyoxypropylene glycol (Sannic GL-3000) as a medium, under atmospheric conditions and at room temperature, 100g of maleic anhydride-modified polybutadiene (Ricon130MA20, Mn3600) and 46g of the above-mentioned... The azole compound was stirred for 3 hours to allow it to react, thus synthesizing polymer particles 7 dispersed in polyoxypropylene glycol. The molar ratio of maleic anhydride groups to NH2 groups in the above-mentioned raw materials was 1.1. The crosslinking sites formed by the above-mentioned crosslinking reaction have amide bonds.
[0323] The average particle size of polymer particles 7 is 10 μm, and the concentration of polymer particles 7 in the above dispersion is 33% by mass. The glass transition temperature of polymer particles 7 is +10 °C. The medium (polyoxypropylene glycol) in the above dispersion is liquid at 23 °C.
[0324] <<Preparation of the Composition>>
[0325] The components in column A of the main agent of each embodiment in Tables 1 and 2 (hereinafter referred to as each table) were used according to the composition (parts by mass) shown in the same table, and these components were mixed using a stirrer under a nitrogen flow to prepare the main agent (A). The curing agent (B) of each embodiment was also prepared in the same way.
[0326] In the preparation of the above-mentioned main agent and curing agent, polymer particles 1 to 7 are used in a mixture with the medium.
[0327] In the tables below, the net weight (amount excluding the medium) of each polymer particle is shown in columns 1 to 7. Furthermore, the content of polymer particles (X) in the total composition does not include the content of the medium that can be used in the manufacture of polymer particles (X).
[0328] In Example 7, the "100 parts by mass" in the "urethane prepolymer 1" column of the main agent refers to 100 parts by mass of urethane prepolymer used as a medium for dispersing polymer particles 6 (39 parts by mass) after manufacturing polymer particles 6. No urethane prepolymer was subsequently added in the main agent of Example 7. The "urethane prepolymer 1" column of Example 9 is the same as above.
[0329] In Examples 1-6, 8, and 9, the "60 parts by weight" in the "Polyol 1" column of the curing agent (B) refers to the total amount of the medium accompanying the polymer particles (X) used in the curing agent (B) and the polyol 1 subsequently added thereto. The amount of polyol 1 subsequently added to the curing agent (B) is as follows.
[0330] (The amount of polyol 1 subsequently added to the curing agent (B))
[0331] Example 1: 13 parts by weight
[0332] Example 2: 1 part by weight
[0333] Example 3: 0 parts by weight
[0334] Example 4: 2 parts by weight
[0335] Example 5: 0 parts by weight
[0336] Example 6: 0 parts by weight
[0337] Example 8: 13 parts by weight
[0338] Example 9: 36 parts by weight
[0339] Using the main agent (A) and curing agent (B) prepared as described above in each embodiment, they are mixed using a mixer to obtain a composition.
[0340] • Equivalent ratio of isocyanate groups to active hydrogen groups *1
[0341] The equivalent ratio (molar ratio of all isocyanate groups to all active hydrogen-containing groups) of the total amount of the mixture of main agent (A) and curing agent (B) (the composition of the present invention) is shown in the "Equivalent Ratio of Isocyanate Groups to Active Hydrogen-Containing Groups" in each table. *1 In the column.
[0342] It should be noted that the amino groups (groups in which hydrogen atoms are bonded to nitrogen atoms) of each polymer particle, which are composed of active hydrogen groups, do not contain urethane bonds, urea bonds, or amide bonds (the same applies below).
[0343] Furthermore, as mentioned above, the molar ratio of maleic anhydride groups to NH2 groups in the manufacture of polymer particles 4 and 7 is 1.0 or 1.1. Therefore, polymer particles 4 and 7 can theoretically possess carboxylic anhydride and / or be derived from... The amino group resulting from the hydrolysis of the azole ring acts as an active hydrogen group, but the carboxylic anhydride group and the aforementioned amino group that polymer particles 4 and 7 can possess are not added to the "isocyanate group / active hydrogen group equivalence ratio". *1 The phrase "containing active hydrogen groups" refers to the phrase "isocyanate group / amino group equivalent ratio" mentioned later. *2 "and "equivalent ratio of amino to hydroxyl groups" *3 The same applies to the "amino" in "".
[0344] • Equivalent ratio of isocyanate group to amino group *2
[0345] The equivalent ratio (molar ratio of all isocyanate groups to all amino groups) of the total amount of the mixture of main agent (A) and curing agent (B) (the composition of the present invention) is shown in the "Equivalent Ratio of Isocyanate Groups to Amino Groups" of each table. *2 The above list of amino groups includes the amino groups found in, for example, polyamines listed in the tables.
[0346] • Equivalent ratio of amino to hydroxyl groups *3
[0347] The equivalent ratio of all amino groups to all hydroxyl groups (molar ratio of all amino groups to all hydroxyl groups) in the total amount of the mixture of main agent (A) and curing agent (B) (the composition of the present invention) is shown in the "Equivalent Ratio of Amino / Hydroxy Groups" of each table. *3 The above list of amino groups includes the amino groups found in, for example, polyamines listed in the tables.
[0348] <<Evaluation>>
[0349] The compositions prepared as described above were evaluated as follows. The results are shown in the tables.
[0350] <Sample Modulation>
[0351] • Solidified product (P)
[0352] As described above, each composition was placed at 23°C and 55% RH (relative humidity) for 7 days to allow each composition to cure, resulting in a cured product (P) of the two-component curing adhesive composition (total).
[0353] Using the cured products (P) obtained as described above, the tanδ, fatigue durability, and elongation at break, which will be discussed later, were evaluated.
[0354] ·Cured product (M), (N)
[0355] The components in column (A) of each embodiment in the following tables are used according to the compositions (parts by mass) shown in the same tables. These components are mixed using a stirrer under a nitrogen atmosphere to prepare the main agent (A). The curing agent (B) of each embodiment is also prepared in the same way. In the preparation of the above main agent, polymer particles and the accompanying medium are not used. The same applies to the curing agent (B).
[0356] Mix the above-mentioned two-component curable adhesive compositions to prepare the remaining portion excluding polymer particles (X) and the accompanying medium. Place the remaining portion at 23°C and 55% RH (relative humidity) for 7 days to cure, and obtain the cured product (M) or (N) of the remaining portion.
[0357] • Polymer microparticles (X): Cured product (H)
[0358] In the synthesis of polymer particles 1 to 7 described above, no medium was used. The remaining components were placed at 23°C and 55% RH (relative humidity) for 7 days to cure the components and obtain a cured product (H). This cured product (H) was then used as polymer particles (X).
[0359] <tanδ>
[0360] For each cured product (P), (M), (N), and (H) obtained as described above, dynamic viscoelasticity was measured under the conditions of strain 0.01%, frequency 100 Hz, and heating rate 5 °C / min. The tanδ was measured by forced elongation vibration within the temperature range of -40 °C to +80 °C.
[0361] The minimum and maximum values of tanδ for the cured material (P) at -40℃, +20℃, and 80℃, and in the temperature range from -40℃ to +80℃, are shown in the respective tables.
[0362] [Evaluation criteria for attenuation in this invention]
[0363] In this invention (including methods 1 and 2 as a whole), the attenuation was evaluated based on whether the tanδ of the cured material (P) was 0.15 or higher in the temperature range of -40°C to +80°C. That is, in this invention, when the tanδ is 0.15 or higher in the entire range of -40°C to +80°C, the attenuation is evaluated as excellent.
[0364] The larger the minimum value of tanδ is compared to 0.15, the better the attenuation performance.
[0365] On the other hand, if the tanδ of the cured material (P) is less than 0.15 in at least a portion of the temperature range of -40°C to +80°C, it is evaluated as having poor attenuation.
[0366] The minimum and maximum values of tanδ for the cured materials (M), (N), and (H) in the temperature range of -40℃ to +80℃ are shown in the respective tables.
[0367] Fatigue Endurance
[0368] Using the compositions obtained as described above, fatigue durability evaluation samples were prepared under the following conditions, and tensile shear fatigue characteristics tests were conducted at a stress amplitude of 2.8 MPa in accordance with JIS K6864.
[0369] • Type of material to be bonded: electrodeposited steel plate
[0370] • Surface treatment method: The surface was cleaned by wiping it with solvent.
[0371] • Application method and curing conditions of the compositions: Apply the compositions obtained as described above to the materials to be bonded using a caulking gun. Curing is carried out at 23°C, 55% RH, for 7 days.
[0372] • Average thickness of adhesive layer: 30μm
[0373] [Evaluation criteria for fatigue durability in this invention]
[0374] The above samples were subjected to stress amplitudes of 3.6 MPa and repeated at least 10 times. 7 If no fracture occurs under the given conditions, it is rated as having the best fatigue durability and is designated as "AAA".
[0375] The above samples were subjected to a stress amplitude of 3.2 MPa and a repetition count of at least 10. 7 The sample did not fracture under the condition of repeated stress amplitude of 3.6 MPa, but the above sample did not fracture under the condition of repeated stress amplitude of 10 times. 7 If fracture occurs under the given conditions, the fatigue durability is rated as excellent and is designated as "AA".
[0376] The above samples were subjected to stress amplitudes of 2.8 MPa and repeated at least 10 times. 7 The sample did not fracture under the condition of repeated stress amplitude of 3.2 MPa, but the above sample did not fracture under the condition of repeated stress amplitude of 10. 7 If fracture occurs under the given conditions, the fatigue durability is rated as slightly excellent, and is designated as "A".
[0377] In this invention (including methods 1 and 2 as a whole), when the above evaluation is A or above, it is considered to have excellent fatigue durability.
[0378] On the other hand, in the above-mentioned samples, the stress amplitude was 2.8 MPa and the number of repetitions was less than 10. 7 If a fracture occurs at this time, it is evaluated as having poor fatigue durability and is denoted as "B".
[0379] <Elongation at break, tensile modulus>
[0380] Using the cured materials obtained as described above, dumbbell-shaped No. 3 test pieces (2 mm thick) were made.
[0381] For the cured material (P), the above test piece was used to conduct a tensile test according to JIS K6251. Under the conditions of a temperature of 20°C and a crosshead speed (tensile speed) of 200 mm / min, the markings for measuring the elongation at break were marked at 20 mm intervals, and the elongation at break (elongation at break) was measured.
[0382] In addition, for the cured materials (M), (N), and (H), the tensile modulus of elasticity was determined using the least squares method based on all points between 0.1% and 1% strain.
[0383] (Evaluation Criteria)
[0384] • Elongation at break of the cured product (P)
[0385] From the viewpoint of superior fatigue durability, the elongation at break of the cured material (P) is preferably 50% or more, and more preferably 100 to 1000%.
[0386] (Evaluation criteria under Method 1)
[0387] Method 1 was also evaluated according to the following benchmarks.
[0388] • The tensile modulus of elasticity of the cured product (M) and the maximum and minimum values of tanδ of the cured product (H).
[0389] When the cured product (P) is Method 1, the cured product (M) obtained by curing the matrix (excluding polymer particles (X) in the two-component curing adhesive composition) (or the remaining part in the two-component curing adhesive composition excluding polymer particles (X) and the medium) has a tensile elastic modulus of 5 MPa or more, and the minimum value of the loss tangent of the polymer particles (X) (i.e., the cured product (H)) is 0.05 or more under the above-mentioned specific conditions. It is evaluated that the fatigue durability and attenuation are superior, and the fatigue durability and attenuation can be balanced at a higher level.
[0390] The greater the tensile modulus of the cured material (M) compared to 5 MPa, the better its fatigue durability.
[0391] The larger the minimum value of the loss tangent of the polymer microparticle (X) is compared to 0.05, the better the attenuation performance.
[0392] (Evaluation benchmark under Method 2)
[0393] Method 2 was also evaluated based on the following criteria.
[0394] Minimum tanδ of cured product (N) and tensile modulus of cured product (H)
[0395] When the cured product (P) is Method 2, the maximum value of the loss tangent of the cured product (N) obtained by curing the matrix (excluding polymer particles (X) in the two-component curing adhesive composition) (or the remaining part in the two-component curing adhesive composition excluding polymer particles (X) and the medium) is 0.3 or more under the specific conditions described above, and the tensile modulus of the polymer particles (X) (i.e., the cured product (H)) is 5 MPa or more, it is evaluated that the fatigue durability and attenuation are superior, and the fatigue durability and attenuation can be balanced at a higher level.
[0396] The larger the maximum value of the loss tangent of the solidified material (N) is compared to 0.3, the better its attenuation performance.
[0397] The greater the tensile modulus of the cured material (P) compared to 5 MPa, the better its fatigue durability.
[0398] Table 1
[0399]
[0400] Table 2
[0401]
[0402] Table 3
[0403]
[0404] Table 4
[0405]
[0406] Details of each component shown in the tables are as follows.
[0407] <Main Agent (A)>
[0408] (Carbamate prepolymer)
[0409] • Carbamate prepolymers 1, 2, and 4: Carbamate prepolymers 1, 2, and 4 prepared as described above.
[0410] (polymer particles (X))
[0411] • Polymer microparticles 6: Polymer microparticles 6 prepared as described above
[0412] ·Carbon black: 200MP, manufactured by Nippon Chemical Co., Ltd.
[0413] ·Calcium carbonate 1: Heavy calcium carbonate, Separo S, manufactured by Maruo Calcutta Co., Ltd.
[0414] Plasticizer: Diisononyl phthalate, manufactured by Jeyplasia Co., Ltd.
[0415] <Curing Agent (B)>
[0416] (Compounds containing active hydrogen groups)
[0417] • Polyol 1: Polypropylene glycol, Sannyx GL-3000, manufactured by Sanyo Chemical Co., Ltd. OH is trifunctional.
[0418] It should be noted that when polymer particles (X) of polyol as a medium are added to curing agent (B), the polyol as the medium is counted in polyol 1.
[0419] (polymer particles (X))
[0420] • Polymer microparticles 1-5, 7: Polymer microparticles 1-5, 7 prepared as described above
[0421] • Comparative polymer particles 1: Prepared as a mixture of comparative polymer particles 1 and polyoxypropylene glycol as a medium, as described below.
[0422] Using a paint mill (S-43 / 4X11, Inoue Manufacturing Co., Ltd.), 15 parts by mass of polymethacrylic acid microparticles (product number: XX-2851Z, manufactured by Sekisui Chemicals Co., Ltd., microparticle concentration: 100% by mass, average particle size: 0.3 μm, glass transition temperature: 100°C) as comparative polymer microparticle 1 and 100 parts by mass of polyoxypropylene glycol (Sunnyx GL-3000) as a medium were mixed and homogenized. The above-mentioned polymethacrylic acid microparticles do not contain active hydrogen groups.
[0423] ·Polyamine: Diethylmethylphenylenediamine, DETDA, manufactured by Mitsui Chemicals Fiber Co., Ltd.
[0424] ·Calcium carbonate 2: Light calcium carbonate, Calcium Carbon 200, manufactured by Maruo Calcium Co., Ltd.
[0425] ·Silica: Rikoli QS-102S, manufactured by Tokusuma Co., Ltd.
[0426] As can be seen from the results shown in the tables, the composition of the present invention can achieve both high fatigue durability and high attenuation.
[0427] On the other hand, for Comparative Example 1, which does not contain the polymer particles (X) used to improve attenuation in Method 1 above, although the fatigue durability of the cured product obtained by curing the composition as a whole is excellent, the minimum value of the loss tangent of the cured product is less than 0.15 in a part of the temperature range of -40°C to +80°C, and the attenuation is poor.
[0428] In addition, for Comparative Example 3, which does not contain polymer particles (X) but instead contains polymer particles with a Tg higher than 80°C, although the fatigue durability of the cured product obtained by curing the composition as a whole is excellent, the minimum value of the loss tangent of the cured product is less than 0.15 in a part of the temperature range of -40°C to +80°C, and the attenuation is poor.
[0429] For Comparative Example 2, which does not contain the polymer particles (X) used to improve fatigue durability in Method 2 above, although the cured product obtained by curing the composition as a whole has excellent attenuation properties, the fatigue durability of the cured product is poor.
[0430] In addition, for Comparative Example 4, which does not contain polymer particles (X) but instead contains polymer particles with a Tg higher than 80°C, the fatigue durability of the obtained cured product is poor.
[0431] Explanation of reference numerals in the attached figures
[0432] 10. Cured product (P)
[0433] 12. Solidified matrix
[0434] 14 Polymer Particles (X)
Claims
1. A two-component curing adhesive composition having a main agent (A) and a curing agent (B), wherein the main agent (A) comprises a urethane prepolymer (a1) having an isocyanate group. At least one of the main agent (A) and the curing agent (B) comprises polymer particles (X) with an average particle size of 0.01 to 200 μm. The glass transition temperature of the polymer particles (X) is in the range of -40℃ to +80℃. The content of the polymer microparticles (X) is more than 5% by mass of the total amount of the two-component curing adhesive composition. The loss tangent of the cured product (P) obtained by curing the two-component curable adhesive composition is greater than 0.15 under the conditions of -40℃ to +80℃ and 100Hz. In the tensile shear fatigue property test conducted according to JIS K6864, the cured material (P) was subjected to a stress amplitude of 2.8 MPa and a repetition count of 10. 7 Under these conditions, no fracture occurs. The cured product (M) obtained by curing the remaining portion of the two-component curable adhesive composition, excluding the polymer particles (X), has a tensile elastic modulus of 5 MPa or higher. The minimum loss tangent of the polymer particles (X) measured under conditions of -40℃ to +80℃ and a frequency of 100Hz is greater than 0.
05. The polymer particles (X) comprise a polymer obtained by reacting a polyisocyanate compound (x1) with at least one compound (x2) selected from polyol compounds, polyamine compounds and potential polyamine compounds.
2. A two-component curing adhesive composition having a main agent (A) and a curing agent (B), wherein the main agent (A) comprises a urethane prepolymer (a1) having an isocyanate group. At least one of the main agent (A) and the curing agent (B) comprises polymer particles (X) with an average particle size of 0.01 to 200 μm. The glass transition temperature of the polymer particles (X) is in the range of -40℃ to +80℃. The content of the polymer microparticles (X) is more than 5% by mass of the total amount of the two-component curing adhesive composition. The loss tangent of the cured product (P) obtained by curing the two-component curable adhesive composition is greater than 0.15 under the conditions of -40℃ to +80℃ and 100Hz. In the tensile shear fatigue property test conducted according to JIS K6864, the cured material (P) was subjected to a stress amplitude of 2.8 MPa and a repetition count of 10. 7 Under these conditions, no fracture occurs. The cured product (M) obtained by curing the remaining portion of the two-component curable adhesive composition, excluding the polymer particles (X), has a tensile elastic modulus of 5 MPa or higher. The minimum loss tangent of the polymer particles (X) measured under conditions of -40℃ to +80℃ and a frequency of 100Hz is greater than 0.
05. The polymer particles (X) comprise a polymer obtained by reacting a maleic anhydride-modified oligomer (x3) with at least one compound (x4) selected from polyols, polyamines, and potential polyamines.
3. A two-component curing adhesive composition having a main agent (A) and a curing agent (B), wherein the main agent (A) comprises a urethane prepolymer (a1) having an isocyanate group. At least one of the main agent (A) and the curing agent (B) comprises polymer particles (X) with an average particle size of 0.01 to 200 μm. The glass transition temperature of the polymer particles (X) is in the range of -40℃ to +80℃. The content of the polymer microparticles (X) is more than 5% by mass of the total amount of the two-component curing adhesive composition. The loss tangent of the cured product (P) obtained by curing the two-component curable adhesive composition is greater than 0.15 under the conditions of -40℃ to +80℃ and 100Hz. In the tensile shear fatigue property test conducted according to JIS K6864, the cured material (P) was subjected to a stress amplitude of 2.8 MPa and a repetition count of 10. 7 Under these conditions, no fracture occurs. The cured product (N) obtained by curing the remaining portion of the two-component curable adhesive composition excluding the polymer particles (X) has a minimum loss tangent of 0.05 or higher, measured under conditions of -40°C to +80°C and 100Hz. The tensile elastic modulus of the polymer particles (X) is greater than 5 MPa. The polymer particles (X) comprise a polymer obtained by reacting a polyisocyanate compound (x1) with at least one compound (x2) selected from polyol compounds, polyamine compounds and potential polyamine compounds.
4. A two-component curing adhesive composition having a main agent (A) and a curing agent (B), wherein the main agent (A) comprises a urethane prepolymer (a1) having an isocyanate group. At least one of the main agent (A) and the curing agent (B) comprises polymer particles (X) with an average particle size of 0.01 to 200 μm. The glass transition temperature of the polymer particles (X) is in the range of -40℃ to +80℃. The content of the polymer microparticles (X) is more than 5% by mass of the total amount of the two-component curing adhesive composition. The loss tangent of the cured product (P) obtained by curing the two-component curable adhesive composition is greater than 0.15 under the conditions of -40℃ to +80℃ and 100Hz. In the tensile shear fatigue property test conducted according to JIS K6864, the cured material (P) was subjected to a stress amplitude of 2.8 MPa and a repetition count of 10. 7 Under these conditions, no fracture occurs. The cured product (N) obtained by curing the remaining portion of the two-component curable adhesive composition excluding the polymer particles (X) has a minimum loss tangent of 0.05 or higher, measured under conditions of -40°C to +80°C and 100Hz. The tensile elastic modulus of the polymer particles (X) is greater than 5 MPa. The polymer particles (X) comprise a polymer obtained by reacting a maleic anhydride-modified oligomer (x3) with at least one compound (x4) selected from polyols, polyamines, and potential polyamines.
5. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the cured product (P) has an elongation at break of 50% or more.
6. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the curing agent (B) comprises a polyol compound (b1) and / or a polyamine compound (b2).
7. The two-component curing adhesive composition according to claim 6, wherein the polyol compound (b1) comprises at least one polyol compound selected from polyoxyethylene polyol, polyoxypropylene polyol, polyoxyethylene polyoxypropylene polyol, polybutadiene polyol, polyisoprene polyol, polyacrylic polyol, and partially modified compounds obtained by partially modifying each of these compounds.
8. The two-component curing adhesive composition according to claim 1 or 2, wherein the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) with a polyol compound (a3) in such a manner that the equivalent ratio of the isocyanate groups in the polyisocyanate compound (a2) to the hydroxyl groups in the polyol compound (a3) is 1.5 to 14. The curing agent (B) comprises a polyol compound (b1) and a polyamine compound (b2). The isocyanate group in the main agent (A) has an equivalent ratio of 0.8 to 4 to the active hydrogen-containing group in the curing agent (B). The isocyanate group in the main agent (A) has an equivalent ratio of 1.2 to 6 to the amino group in the polyamine compound (b2).
9. The two-component curing adhesive composition according to claim 8, wherein the polyol compound (a3) comprises at least one polyol compound selected from polyester polyols, polytetramethylene ether glycol, polycarbonate polyols, polycaprolactone polyols, and partially modified compounds obtained by partially modifying each of these compounds.
10. The two-component curing adhesive composition according to claim 3 or 4, wherein the urethane prepolymer (a1) is obtained by reacting a polyisocyanate compound (a2) with a polyol compound (a3) in such a manner that the equivalent ratio of the isocyanate groups in the polyisocyanate compound (a2) to the hydroxyl groups in the polyol compound (a3) is 1.5 to 2.
5. The curing agent (B) comprises a polyol compound (b1) and a polyamine compound (b2). The isocyanate group in the main agent (A) has an equivalent ratio of 0.8 to 4 to the active hydrogen-containing group in the curing agent (B). The isocyanate group in the main agent (A) has an equivalent ratio of 1.5 to 8.0 to the amino group in the polyamine compound (b2).
11. The two-component curing adhesive composition according to claim 10, wherein the polyol compound (a3) comprises at least one polyol compound selected from polyoxypropylene glycol, polybutadiene polyol, polyisoprene polyol, polyacrylic acid polyol, and partially modified compounds obtained by partially modifying each of these compounds.
12. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the maximum value of the loss tangent of the cured product (P) measured under conditions of temperature range of -40°C to +80°C and frequency of 100Hz is 0.3 or more.
13. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the polymer microparticles (X) are obtained by crosslinking a crosslinking oligomer in at least one medium selected from water, an organic solvent and oligomers to produce the polymer microparticles.
14. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the polymer microparticles (X) are obtained by crosslinking a crosslinking oligomer in at least one medium selected from water, an organic solvent, and a polymer to produce the polymer microparticles.
15. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the polymer microparticles (X) are obtained by crosslinking a crosslinked polymer in at least one medium selected from water, organic solvents and oligomers to form polymer microparticles.
16. The two-component curing adhesive composition according to any one of claims 1 to 4, wherein the polymer microparticles (X) are obtained by crosslinking a crosslinked polymer in at least one medium selected from water, organic solvents and polymers to form polymer microparticles.
Citation Information
Patent Citations
Two liquid urethane adhesive composition
JP2017082118A
Two-pack urethane adhesive composition
CN107075338A
Adhesive composition, resin material treated therewith and rubber article reinforced with the resin material
JP2001019927A